Beef Consumption and Cardiovascular Disease Risk Factors: A Systematic Review and Meta-analysis of Randomized Controlled Trials - Lisa M Sanders; Orsolya M Palacios; Meredith L Wilcox; Kevin C Maki (Current Developments in Nutrition)
Background: Results from observational studies suggest associations of red meat intake with increased risk of cardiovascular disease (CVD); however, RCTs have not clearly demonstrated a link between red meat consumption and CVD risk factors. Further, the specific effects of beef, the most consumed red meat in the United States, have not been extensively investigated. Objectives: This study aimed to perform a systematic review and meta-analysis of RCT data evaluating the effects of minimally or unprocessed beef intake on CVD risk factors in adults. Methods: A search of the literature was conducted using PubMed and CENTRAL databases. RCTs in adults that provided diets with fresh or minimally processed beef were included. Data were extracted, and pooled estimates from random-effects models were expressed as standardized mean differences (SMDs) between the beef intervention and comparator intervention with less or no beef. Sensitivity and subgroup analyses were also performed. Results: Twenty relevant RCTs that met the criteria were included. Beef intake did not impact blood pressure or most lipoprotein-related variables, including total cholesterol, HDL-cholesterol, triglycerides, non–HDL-cholesterol, apolipoprotein A or B, and VLDL-cholesterol. Beef consumption had a small but significant effect on LDL-cholesterol (0.11; 95% CI: 0.008, 0.20; P = 0.03), corresponding to ∼2.7 mg/dL higher LDL-cholesterol in diets containing more beef than that in low-beef or -o beef comparator diets. Sensitivity analyses show this effect was lost when 1 influential study was removed. Conclusions: Daily unprocessed beef intake do not significantly affect most blood lipids, apolipoproteins, or blood pressures, except for a small increase in LDL-cholesterol compared with diets with less or no beef. Thus, there may be other factors influencing the association of red meat and beef on CVD risk that deserve further investigation.This study was registered at INPLASY as 202420013.